A novel injury paradigm in the central nervous system of adult Drosophila: molecular, cellular and functional aspects - Losada-Pérez, María (Dis Model Mech, 2021)
The mammalian central nervous system (CNS) exhibits limited regenerative capacity and the mechanisms that mediate its regeneration are not fully understood. Here, we present a novel experimental design to damage the CNS by using a contusion injury paradigm. The design of this protocol allows the study of long-term and short-term cellular responses, including those of the CNS and the immune system, and of any implications regarding functional recovery. We demonstrate for the first time that adult Drosophila melanogaster glial cells undergo spontaneous functional recovery following crush injury. This crush injury leads to an intermediate level of functional recovery after damage, which is ideal to screen for genes that facilitate or prevent the regeneration process. Here, we validate this model and analyse the immune responses of glial cells as a central regulator of functional regeneration. Additionally, we demonstrate that glial cells and macrophages contribute to functional regeneration through mechanisms involving the Jun N-terminal kinase (JNK) pathway and the Drosophila protein Draper (Drpr), characteristic of other neural injury paradigms. We show that macrophages are recruited to the injury site and are required for functional recovery. Further, we show that the proteins Grindelwald and Drpr in Drosophila glial cells mediate activation of JNK, and that expression of drpr is dependent on JNK activation. Finally, we link neuron-glial communication and the requirement of neuronal vesicular transport to regulation of the JNK pathway and functional recovery. This article has an associated First Person interview with the first author of the paper.